he Effect of the Use of L. plantarum Starter on a Complete Ration Silage Made from Water Hyacinth on Consumption of Nitrogen Free Extract (NFE), Partial Volatile Fatty Acids (VFA) Production, Methane Production, and Blood Glucose Concentration of Sheep - E. Ekawati; A. Muktiani; . Sunarso (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2015)
This study aimed to determine the use of L. plantarum starter on a complete ration silage made from water hyacinth on consumption of nitrogen free extract (NFE), partial volatile fatty acids (VFA) production, methane production, and blood glucose concentration of sheep. This study used fifteen rams (12 months old with an average body weight of 19 ± 3.98 kg). Sheep were randomly divided into 3 groups of treatment rations, namely the group given: concentrate ration and elephant grass (T0), complete ration silage provided without the addition of L. plantarum starter (T1), and complete ration silage provided with the addition of L. plantarum starter (T2). Ration was formulated isocaloric and isoprotein (CP 13%, TDN 65%). The results showed that the consumption of NFE, the concentration of propionic acid, butyric acid and blood glucose before and post feeding was not significantly different, whereas the concentration of acetic acid, the ratio of C2:C3 and methane production was significantly different (P<0,05) among treatments. The concentration of acetic acid of treatment T0, T1 and T2 was 36.52, 28.86, and 32.43 mM, respectively. Methane concentration was 19.95, 16.08, 17,55 mM, respectively for T0, T1, T2 and glucose concentration was 45.50, 70.30, and 53.24 mg/dl, for treatment T0, T1, T2, respectively. In conclusion, provision of silage ration complete which was provided with or and without L. plantarum starter was much better compared to control ration, (concentrates with elephant grass).